2012
DOI: 10.1080/13803395.2012.692771
|View full text |Cite
|
Sign up to set email alerts
|

Antisaccade performance in Korsakoff patients reveals deficits in oculomotor inhibition

Abstract: Oculomotor inhibition reflects the ability to suppress an unwanted eye movement. The goal of the present study was to assess oculomotor inhibition in patients with Korsakoff's syndrome (KS). To this end, an antisaccade task was employed in which an eye movement towards an onset stimulus has to be inhibited, and a voluntary saccade has to be executed in the opposite direction. Compared to the results of a matched control group, patients showed a higher percentage of intrusive saccades, made more antisaccade err… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…This finding suggests that the more severely impaired patients did gain greater benefit from the learning techniques than less severely impaired patients. A possible explanation for this finding is that long-term memory and executive functioning, two cognitive domains that are essentially restrained in Korsakoff's syndrome (Van der Stigchel et al, 2012), negatively affect learning mechanisms in learning an instrumental activity of daily living. This finding is in line with an earlier study by Klimkowicz-Mrowiec and colleagues (2008) suggesting that patients with more severe amnesia due to Alzheimer's dementia outperformed patients with less severe amnesia on a task intended to assess procedural learning.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This finding suggests that the more severely impaired patients did gain greater benefit from the learning techniques than less severely impaired patients. A possible explanation for this finding is that long-term memory and executive functioning, two cognitive domains that are essentially restrained in Korsakoff's syndrome (Van der Stigchel et al, 2012), negatively affect learning mechanisms in learning an instrumental activity of daily living. This finding is in line with an earlier study by Klimkowicz-Mrowiec and colleagues (2008) suggesting that patients with more severe amnesia due to Alzheimer's dementia outperformed patients with less severe amnesia on a task intended to assess procedural learning.…”
Section: Discussionmentioning
confidence: 97%
“…Also, forming associations between temporal order information and spatial information is severely hampered (Postma, Van Asselen, Keuper, Wester, & Kessels, 2006). Besides problems with contextual memory, deficits in executive functions have also been reported in Korsakoff's syndrome (Brand et al, 2005;Jacobsen, Acker, & Lishman, 1990; Van der Stigchel, Reichenbach, Wester, & Nijboer, 2012). The combination of memory and executive deficits has a massive impact on the patient's ability to carry out daily routines.…”
Section: Introductionmentioning
confidence: 96%
“… Oudman et al 2011 18 KS 20 HC Implicit Contextual Learning KS patients showed intact ability to to find a target among a number of distractors during visual search after repetition and without conscious recollection. Van Tilborg et al 2012 Serial reaction time task Pattern learning task Implicit motor learning occurred in both groups of participants on the serial reaction time task; however, on the Pattern Learning Task, the percentage of errors did not increase in the Korsakoff group in the random test phase, which is indicative of less implicit learning. Kessels et al 2007 10 KS Route learning task Both errorless learning and trial-and-error learning supported a route learning task.…”
Section: Procedural Learning In Korsakoff’s Syndromementioning
confidence: 98%
“…In KS, there is also a temporally-graded memory deficits for remote memory (retrograde amnesia) which characteristically extends back many years or decades (Kopelman et al 1999 ). Commonly, executive deficits are present, such as problems with inhibition of behavior, high interference of information sensitivity, poor judgment, poor planning abilities, problem solving inabilities, and perseverative responses (Van der Stigchel et al 2012 ; Oscar-Berman 2012 ). The cognitive problems in KS are caused by diencephalic atrophy of the brain, with damage to the anterior nucleus of the thalamus, the mammillary bodies and the corpus callosum as the most common features of KS that are not caused by the direct neurotoxic effects of alcohol (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Significant eye movement abnormalities include hypometria, slow and inaccurate saccades and impaired smooth pursuit [86, 87]. Patients with Korsakoff’s syndrome also make more directional errors on the antisaccade task [88]. Wernicke’s encephalopathy is not predominantly cerebellar, but like other neurodegenerative conditions also affects extracerebellar brainstem regions including those responsible for the saccade burst generation [81, 89].…”
Section: Introductionmentioning
confidence: 99%